'Staying' as climate change adaptation strategy: A proposed research agenda. Issue 121 (May 2021) - Pemberton, Simon; Tripathy Furlong, Basundhara; Scanlan, Oliver; Koubi, Vally; Guhathakurta, Meghna; Hossain, Md. Khalid; Warner, Jeroen; Roth, Dik
Highlights: Staying can be an alternate climate change adaptation strategy. Staying and mobility are re-imagined with ideas of resilience and evolution. Four key research areas linking climate change, staying and resilience. Historical context and translocal networks shape immobility. Equity and governance identify population differentials and choice of im(mobility). Abstract: This paper brings work on mobility and 'staying' together with theoretical ideas of resilience to consider responses to climate change. To date, the majority of work that has explored the impacts of climate change on human populations has taken a migration-centred perspective, with an emphasis on mobility as a key response in crises, including extreme climatic events and civil conflict. However, evidence suggests that people may alternatively – and pro-actively – adopt a different approach involving "staying" as a climate change adaptation strategy. This is important as recent evolutionary approaches to resilience have highlighted how resilience is an on-going process of adaptation which emphasises the temporal, fluid and open-ended aspects of individuals' experiences and practices in shaping everyday lives. In turn, this means that individuals' experiences and practices can lead to different strategies of staying (as well as moving) in the face of climate change. Consequently, the paper highlights four key areas where more research is required in order to explore the links between climate change, 'staying' and resilience. These include the importance of historical context in disentangling and contextualising the "multicausal" nature of individuals' mobility decisions; translocal networks in shaping mobility or immobility; the influence of equity, diversity and gendered social expectations on staying; and the importance of governance responses in facilitating resilience, adaptation and subsequent decisions by individuals to stay or move.